PENYUSUNAN NASKAH AKADEMIK PEMEKARAN KELURAHAN KATOBENGKE KECAMATAN BETOAMBARI - Said, Rosnani; Faharuddin, Faharuddin; Mande, Henni; Nuryati, Nuryati (Unit Publikasi dan Jurnal Sekolah Tinggi Ilmu Ekonomi Tri Dharma Nusantara Makassar, 2023)
The problems of this research are: (1). What problems are faced by the people of Katobengke Village which are the reasons for the need to prepare a Draft Regional Regulation for the Expansion of Katobengke Village? (2). What are the philosophical, sociological and juridical considerations/foundations for drafting the Draft Regional Regulation in question? (3). What are the implications of implementing the Academic Text for Village Expansion which will be regulated in Regional Regulations on the Economic, Socio-Cultural and Environmental Aspects of the Village. The research objectives are: (1). Formulate the problems faced by the Katobengke community of Baubau City which are the reasons for the need to prepare a Draft Regional Regulation for the Expansion of the Katobengke Village. (2). Formulate philosophical, sociological and juridical considerations/foundations for drafting the Draft Regional Regulation for the Expansion of Katobengke Village. (3). Outlining the Implications of Implementing the Academic Text for Urban Village Expansion which will be regulated in Regional Regulations regarding Economic, SocioCultural and Environmental Aspects. The expansion of the Katobegke sub-district in Betoambari District is based on Government regulations. Manuscript of research results (legal studies & other research results) on a particular problem. Manuscript of research results (legal studies & other research results) on a particular problem. As a solution to society's legal problems and needs. (Attachment 1. Law No. 12/2011). Created in the context of preparing the Baubau City Raperda concerning the Expansion of the Katobengke Village. This research is based on normative legal/juridical research, namely highlighting law as something to aspire to (das solen), secondary data sources/library research. Data collection steps include: (a) inventory of regulations per law: (i) related to the formal & material principles of drafting the Draft Regional Regulation; (ii) other relevant legislation; (iii) non-legal materials (b) analysis (qualitative), reduction, explanation, drawing conclusions (Miles & Huberman, 1992). The result of this research is the formation of an academic text and draft regional regulations regarding the formation of Katobengke Village, Betoambari District